IMPLEMENTATION OF THE E-VOTING SYSTEM IN THE ELECTION OF THE OSIS SMA DHARMA PANCASILA VOCATIONAL SCHOOL BASED ON WEB-BASED METHODS RAPID APPLICATION DEVELOPMENT (RAD) - Eka Hayana Hasibuan; Roy Nuary Singarimbun; Baginda Harahap (Sean Institute, 2022)
In manual voting often results in errors in vote counting, The goal to be achieved from making this e-voting application is to be able to assist committee officers in calculating the number of voters and election results quickly and accurately. For data analysis techniques using Rapid Application Development (RAD) method, which is one of the data analysis while to design this application the method used is object-oriented design using the Unified Modeling Language (UML). Based on the analysis of system requirements, a system was created web-based student council chairman election. The choice of a web-based system was due to This website is widely known by the public. So to finish The problem was proposed by a web-based e-voting system. In conclusion with With this application, general elections can run honestly and fairly and can minimize errors that can be made by humans or reduce manipulation and fraud that can occur.